Industrial training report: information technology department Lembaga Kemajuan Kelantan Selatan (KESEDAR) / Ami Aida Omar - Omar, Ami Aida (Perpustakaan Tengku Anis, 2016)
The trainee under industrial training starting from 1 August until December 31 2016 at Lembaga Kemajuan Kelantan Selatan (KESEDAR) Bandar Baru Gua Musang, 18300 Gua Musang, Kelantan. KESEDAR was established to balance the composition of the residents in Southern Kelantan with the northern part of the state, eradicate poverty, and restructure the community. the trainee at the place in information technology department under the supervisor organization Ms. Hasri Rifdi Mamat @ Hamzah. the project that develop the system My-usahawan. The trainee also gained a lot of knowledge and skills that can be used in the future. The industrial training programs run smoothly. Thus, the trainee give some suggestions to solve the problem. The trainee also give a personal opinion about the training industry.